PENGARUH TEHNIK HYPNOBIRTHING TERHADAP PEMBUKAAN SERVIKS DAN PENURUNAN KEPALA PERSALINAN NORMAL PADA IBU PRIMIGRAVIDA KALA I - Muhidayati, Wiwik; Luluk, Sri (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2019)
ABSTRAK Background:   The old Partus may jeopardize  the safety of the mother and fetus, so it is  important   to  pursue   the  progress   of  labor,   especially  for primigravida   mothers. Hypnobirthing technique is one effortto help the progress of laborMethods:  This study was a quasi experiment post  test only with control group. The population  of this research is all mothers of maternal first in BPM Lamongan City Area. The sample was taken by accidental sampling technique and the sample size was 32 respondents, divided into experimental group and control group.  The progress  of labor was measured by four indicators  recorded  in partograf.  namely:  his frequency,  duration  of  his,  cervical opening and decreased head.gResults:  In the control group,  the advancement  of cervical  opening  of the first 4 hours averaged 2.12  cm and most did not progress head-drop. in the experimental group, the advancement  of cervical  opening of the first  4 hours averaged  3.56 cm and most of them progressedmb  head-drop.  The result of independent  T-test showed  cervical opening 0,007; and p-value head decrease of0.000.Conclusion.There   is an influence of hypnobirthing technique on the progress of labor in the mother of primigravida  when I normal. Keywords: Hypnobirthing, cervical opening and head drop, Primigravida